Corporate internal control, capacity utilization and total factor productivity - Xiao Li (PLoS ONE, 2025)
Based on Internal Control (IC) theory and Principal-agent theory, this study explores the impacts of IC on capacity utilization and total factor productivity, and the internal mechanism among them. The results show that effective IC improves total factor productivity and capacity utilization. Sufficient capacity utilization has a mediating effect for the impact of IC and total factor productivity. Heterogeneity discussion shows that with higher environmental uncertainty, effective IC has a more significant marginal effect on total factor productivity and capacity utilization, and sufficient capacity utilization has a greater mediating effect between IC and total factor productivity. Finally, it is suggested that regulators guide enterprises to strengthen IC construction, to improve capacity utilization and total factor productivity. Enterprises facilitate the mechanism that effective IC improves capacity utilization, and increases total factor productivity. This study enriches the literature on IC enabling corporate operation, and has practical significance for shaping competitive advantages.